A permittivity regulating strategy to achieve high-performance electromagnetic wave absorbers with compatibility of impedance matching and energy conservation. (13th January 2017) - Quan, Bin; Liang, Xiaohui; Xu, Guoyue; Cheng, Yan; Zhang, Yanan; Liu, Wei; Ji, Guangbin; Du, Youwei
Abstract : With the variation of permittivity, MoS2 /rGO composites with a broad frequency bandwidth and strong absorbing performance can be obtained due to their optimal compatibility of impedance matching and attenuation loss ability. Abstract : Permittivity plays crucial but reverse roles in impedance matching and attenuation loss in terms of electromagnetic wave absorption. In addition to unilateral superior performance, an ideal absorber needs to take into consideration both impedance matching and energy conservation. In order to acquire absorbing materials with moderate impedance matching and attenuation ability simultaneously, we have fabricated MoS2 /rGO composites via a facile and effective hydrothermal approach. The dielectric constant of the obtained composite can be regulated by varying the molar ratio of the precursors and an optimal balance between impedance matching and energy conservation is eventually obtained upon addition of 6 mL GO. The maximum reflection loss is −67.1 dB at 14.8 GHz and the effective electromagnetic wave absorption bandwidth for RL < −10 dB covers from 12.08 to 18.00 GHz (5.92 GHz) with a small thickness of 1.95 mm. Moreover, the relationship between the matching thickness and the highest reflection loss value has also been discussed in detail. The results not only suggest that the MoS2 /rGO composites developed through a simple procedure here can act as an ideal absorber with strong absorption, a broad frequency bandwidth and small thickness, but also offer a good reference for the design of microwave absorbers, including the compatibility of impedance matching and attenuation loss ability as well as matching thickness.